Partisipasi Pemuda Dalam Pengembangan Desa Wisata Alam di Desa Sendangharjo Lamongan - Husni Mubarok (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2023)
Sendangharjo Village is one of the Area under the auspices of Perum Perhutani KPH Tuban which is also threatened with illegal logging. Development of community-based tourism or Community Based Tourism (CBT) is one of the efforts to preserve the nature and culture of rural communities. Through this activity, economic growth from various community-based economic sectors can also be developed, such as service providers, handicraft sellers, traders and others. The purpose of this study is to find out, describe, and analyze youth applications in the development of the Akar Langit Trinil Natural Tourism Village in Sendangharjo. The method used in this study uses a qualitative descriptive approach with observation, interviews and documentation techniques. The results of this study indicate that with the cooperation of various parties, namely Perhutani KPH Tuban and the local Karang Taruna Youth as well as community participation, the development of the Akar Langit Nature Tourism Village has accelerated. All the people are directly involved in all the activities that are there. Follow-up that needs to be done is to market tourist attractions both through print and electronic media and provide guidance on the development of natural tourism for managers, namely village youth who are there.